2020
DOI: 10.1038/s41598-020-67159-3
|View full text |Cite
|
Sign up to set email alerts
|

Plasma IP-10 and IL-6 are linked to Child-Pugh B cirrhosis in patients with advanced HCV-related cirrhosis: a cross-sectional study

Abstract: We aimed to evaluate the association of plasma biomarkers linked to inflammation (bacterial translocation, inflammatory response, and endothelial dysfunction), coagulopathy, and angiogenesis with the severity of liver cirrhosis (assessed by the Child-Pugh-Turcotte score, CTP) and Child-Pugh B cirrhosis (CTP 7-9) in patients with advanced hepatitis C virus (HCV)-related cirrhosis. We carried out a cross-sectional study in 97 patients with advanced HCV-related cirrhosis (32 HCV-monoinfected and 65 HIV/HCV-coinfe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 36 publications
0
4
0
1
Order By: Relevance
“…A recent article on HIV/HCV-coinfected patients showed that plasma biomarkers of bacterial translocation, inflammation, endothelial dysfunction, and coagulopathy increased with increased liver fibrosis severity, particularly in patients with LSM ≥ 40 KPa ( 35 ). Besides, plasma IP-10 and IL-6 have also been correlated to advanced liver disease (CTP 7-9) ( 42 ). However, the eradication of HCV with antiviral therapy can stop this pathological process of the liver, at least almost entirely ( 34 ).…”
Section: Discussionmentioning
confidence: 99%
“…A recent article on HIV/HCV-coinfected patients showed that plasma biomarkers of bacterial translocation, inflammation, endothelial dysfunction, and coagulopathy increased with increased liver fibrosis severity, particularly in patients with LSM ≥ 40 KPa ( 35 ). Besides, plasma IP-10 and IL-6 have also been correlated to advanced liver disease (CTP 7-9) ( 42 ). However, the eradication of HCV with antiviral therapy can stop this pathological process of the liver, at least almost entirely ( 34 ).…”
Section: Discussionmentioning
confidence: 99%
“…Overt hepatic encephalopathy was diagnosed clinically based on impairment mental status as defined by the West Haven Criteria (WHC) and impairment neuromotor function. It was assessed using psychometric hepatic encephalopathy score (PHES) ( 15 ). Ascites was assessed by physical examination and abdominal ultrasound.…”
Section: Methodsmentioning
confidence: 99%
“…El uso de escalas es importante para determinar el pronóstico de los pacientes que presentan esta entidad pa- tológica puesto que permiten predecir el riesgo de mortalidad según el curso natural de la enfermedad, una de las escalas de mayor aplicación a nivel mundial es el Child Pugh que evalúa el pronóstico de mortalidad, donde a mayor puntaje se incrementa este riesgo 26,27 . Adicionalmente, se ha encontrado que el uso de la escala de Child Pugh continúa siendo relevante para predecir la aparición de coagulopatías puesto que, al clasificar el grado de disfunción hepática, permite identificar la gravedad de la enfermedad y asociarse con un mayor riesgo de sangrados o hemorragias debido a los trastornos de la coagulación [28][29][30] . Teniendo presente lo anterior es importante recalcar que los índices de coagulación (PT, PTT), los factores de coagulación, los parámetros plaquetarios y la función hepática reflejan eficazmente el nivel de lesión hepática, lo cual se relaciona con la gravedad de la lesión hepática, y pueden proporcionar evidencia para el diagnóstico precoz de pacientes con cirrosis con importancia clínica 30 .…”
Section: Discussionunclassified